The production and distribution of lianhuanhua (1949-1966) - Scott, Rebecca (2016)
My doctoral thesis uses the ‘institutional approach’ to analyse the mechanics of the production and distribution of lianhuanhua (comics) from 1949 to 1966. From this analysis, I extrapolate what made the medium unique and therefore what insights lianhuanhua can offer into Maoist ‘political culture’. Lianhuanhua originated in the Republican era and the unique characteristics of its publishing and distribution had important consequences for the medium’s subsequent development after 1949. During the ‘seventeen years’ lianhuanhua functioned as a propaganda tool, supporting political campaigns and celebrating CCP history. Despite these functions however, the themes inherent in the medium were a lot more varied. Analysis reveals that what was allowed and disallowed was considerably more ad hoc than what we might expect of a strictly controlled totalitarian state. Irregular approaches to production and censorship were also mirrored in the lack of an overall national publishing strategy before 1966. Meanwhile, as the producers of an art form which managed to successfully reconcile the inherent contradictions in CCP art policy, lianhuanhua artists developed a complex give and take relationship with Party-State agencies. Comics were disseminated through highly regulated channels, including bookshops, libraries and factories to ensure ‘revolutionary’ content reached a wider audience and Party-State agencies also sought to advocate ‘appropriate’ reading through ‘reading tutorship’. However, these agencies simultaneously faced challenges in regulating the stocks and location of the highly popular lianhuanhua ‘guerrilla vendors’ and this had profound implications for the kinds of content which persisted in circulating in the early PRC.